FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI TUKAR DOLLAR AMERIKA SERIKAT TERHADAP RUPIAH TAHUN 2000–2013 - Rizki Rahma Kusumadewi; Wahyu Widayat (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2014)
Exchange rate is one tool to measure a country’s economic conditions. The growth of a stable currency value indicates that the country has a relatively good economic conditions or stable. This study has the purpose to analyze the factors that affect the exchange rate of the Indonesian Rupiah against the United States Dollar in the period of 2000-2013. The data used in this study is a secondary data which are time series data, made up of exports, imports, inflation, the BI rate, Gross Domestic Product (GDP), and the money supply (M1) in the quarter base, from first quarter on 2000 to fourth quarter on 2013. Regression model time series data used the ARCH-GARCH with ARCH model selection indicates that the variables that significantly influence the exchange rate are exports, inflation, the central bank rate and the money supply (M1). Whereas import and GDP did not give any influence.